Theology Of Christian Education In Matthew 28:16-20 - Harman Ziduhu Laia; Goktondi Pasaribu; Ponco Mujiono Basuki (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2022)
The implementation of Christian Education must be based on correct theological principles, so as not to deviate from Bible truth, and glorify the Lord Jesus, the giver of the task of Christian Education itself. One of the main and important texts on this subject is Matthew 28:16-20 which is known as the Great Commission of the Lord Jesus for all believers, and the task of teaching part of it. Therefore, it is very important to understand the principles of Christian Education theology according to this text. Based on the exegesis study of Matthew 28:16-20, several Christian Education theological principles are put forward in it, namely: (1) Actors of Christian Education must have a loyal character, and be taught about the Bible first so they have teaching skills later; (2) The content or material taught in Christian Education is the teachings of the Lord Jesus; (3) Christian Education must be carried out by all believers, namely they have all the conditions in the first point; (4) Christian Education must function as a means of discipling every new believer (new disciple) to mature their faith; (5) Christian Education must be given to all believers of all ages; (6) Christian Education is the task from the Lord Jesus, the Owner of all power in heaven and on earth, therefore, it is a task that must be carried out; (7) Christian Education must aim to form every believer to become obedient to the teachings of the Lord Jesus; (8) Christian Education actors will be accompanied by the Lord Jesus; (9) Christian Education must be carried out on the basis of the authority of the Lord Jesus.